Pengaruh Edukasi Kesehatan Tentang Cuci Tangan Pakai Sabun (CTPS) Terhadap Tingkat Pengetahuan dan Kepatuhan Siswa MTs Al-Washliyah Stabat - Meutia Nanda; Jihan Fadhillah; Najwa Azzahra; Fidelma Felicia; Sarah Agustina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aimed to analyze the effect of health education on Handwashing with Soap (HWWS) on the knowledge and compliance of students at MTs Al-Washliyah Stabat. A quantitative study with a One Group Pre-Test and Post-Test Design was conducted in April 2026 involving 50 eighth-grade students selected through total sampling. The intervention consisted of lectures, interactive discussions, demonstrations of the six-step handwashing technique, and direct practice. Data were collected using knowledge and compliance questionnaires before and after the intervention and analyzed using descriptive statistics and the paired t-test with a significance level of 0.05. The results showed that the knowledge score increased from 3.12 to 4.84, while the compliance score increased from 5.84 to 8.58 after the intervention. Statistical analysis demonstrated significant differences between pre-test and post-test scores for both variables (p<0.001). Health education was proven effective in improving students' knowledge and compliance regarding proper handwashing with soap, suggesting that continuous school-based health education programs should be implemented.